PENGARUH POLA ASUH ORANG TUA TERHADAP HASIL BELAJAR KOGNITIF SISWA DALAM PEMBELAJARAN MATEMATIKA - Lis Fitriyani, Dhela; Sari, Yunita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the influence of parenting styles on fifth-grade students’ cognitive achievement in mathematics at MI Nurul Huda 02 Keturen. Mathematics, as a fundamental discipline requiring logical and analytical thinking, often presents learning challenges due to its abstract and hierarchical nature. Previous studies highlight the role of family environment in shaping students’ academic outcomes; however, inconsistencies remain between theoretical expectations and actual parental involvement in supporting children’s learning at home. This quantitative ex-post facto research involved 41 students selected through saturated sampling. Data were collected using a validated Likert-scale questionnaire to measure parenting styles (authoritarian, democratic, and permissive) and documentation of students’ semester mathematics scores. Data analysis included normality and linearity tests, followed by multiple linear regression and coefficient of determination analysis using SPSS. The results indicate that parenting styles simultaneously contribute 26.8% to the variance in students’ mathematics achievement (R² = 0.268; R = 0.518). Democratic parenting shows the strongest positive and significant influence (β = 1.329), while authoritarian parenting has a significant negative effect (β = -1.275). Permissive parenting demonstrates a positive but non-significant effect. These findings confirm that parenting style is a significant external factor influencing mathematics learning outcomes, although other factors account for 73.2% of the variance. Strengthening collaboration between parents and schools is therefore essential to optimize students’ academic performance.